Pharmacokinetic/pharmacodynamic modeling of ketoprofen and flunixin at piglet castration and tail‐docking. Issue 5 (14th July 2022) - Nixon, Emma; Chittenden, Jason T.; Baynes, Ronald E.; Messenger, Kristen M.
Abstract: This study performed population‐pharmacokinetic/pharmacodynamic (pop‐PK/PD) modeling of ketoprofen and flunixin in piglets undergoing routine castration and tail‐docking, utilizing previously published data. Six‐day‐old male piglets (8/group) received either ketoprofen (3.0 mg/kg) or flunixin (2.2 mg/kg) intramuscularly. Two hours post‐dose, piglets were castrated and tail docked. Inhibitory indirect response models were developed utilizing plasma cortisol or interstitial fluid prostaglandin E2 (PGE2) concentration data. Plasma IC50 for ketoprofen utilizing PGE2 as a biomarker was 1.2 μg/ml, and ED50 for was 5.83 mg/kg. The ED50 calculated using cortisol was 4.36 mg/kg; however, the IC50 was high, at 2.56 μg/ml. A large degree of inter‐individual variability (124.08%) was also associated with the cortisol IC50 following ketoprofen administration. IC50 for flunixin utilizing cortisol as a biomarker was 0.06 μg/ml, and ED50 was 0.51 mg/kg. The results show that the currently marketed doses of ketoprofen (3.0 mg/kg) and flunixin (2.2 mg/kg) correspond to drug responses of 33.97% (ketoprofen‐PGE2), 40.75% (ketoprofen‐cortisol), and 81.05% (flunixin‐cortisol) of the maximal possible responses. Given this information, flunixin may be the best NSAID to use in mitigating castration and tail‐docking pain at the current label dose.